Sugar Daddies, Airbus solution or liability? (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
We seem to be confronted with multiple long-term policy challenges. Why do these problems come about and how can we limit their impact? A four step agenda for research and public policy shall be considered.